Frostborn - Anders, Lou (Anders, Lou. Thrones & Bones., 2015)
Instead of taking over his family's farm in Norrøngard, Karn would rather play the board game Thrones and Bones, until half-human, half-frost giantess Thianna appears and a family crisis sends them on an adventure, chased by a dragon, undead warriors, an evil uncle, wyverns, and various trolls and giants.